ANALYSIS OF SELF-CONTROL IN MEDIATING THE INFLUENCE OF THE SOCIAL ENVIRONMENT AND ADOLESCENT PERCEPTIONS OF ADOLESCENT ATARAXIA AT THE NAHDLATUL AT-THULAB IPNU IPPNU: PLS-SEM ANALYSIS - Saputra, Yahya Dwi Marta; Hakim, Ahmad Nu'man; Daryono, Rihab Wit (Abjadia : International Journal of Education, 2024)
This research aims to explore the influence of Adolenscent perceptions and Social Environment on teenagers' Ataraxia, as well as the mediating role of self-control in the context of prayer activities in the Nahdlatul At-Thulab IPNU IPPNU assembly. A quantitative survey method was used involving 60 teenagers in the Nahdlatul At-Thulab IPNU IPPNU prayer assembly, using probability sampling techniques with proportionate stratified sampling techniques. Data was collected through a questionnaire with a Likert scale, and data analysis was carried out using relevant statistical techniques. The research results show that there is a positive influence of Adolenscent perceptions and Social Environment on the results of Teenager Ataraxia, with self-control mediating this relationship. The implications of this research include the importance of developing self-control skills and motivation in prayer meetings. Recommendations for further research include exploring other factors that influence adolescent perception, social environment, and self-control, as well as developing prayer activities to understand the dynamics of adolescent ataraxia.